THE MEDIATING EFFECT OF PERSONAL VALUES ON THE INFLUENCE OF HUMAN CAPITAL ON THE PRODUCTION OF ARTISANAL CHEESES - Roldan, Bruna Bresolin; Blasco, Mario Rosique; Roldan, Lucas Bonacina; Palma Revillion, Jean Philippe; Perez de Lema, Domingo Garcia (Revista Brasileira de Gestão e Desenvolvimento Regional, 2023)
This study proposed the identification of personal values and their role as mediation between human capital and the expression of quality. The relationship between these factors in artisanal food production in small companies is still little explored, so this work has the objective of bringing advances in this theme. For the analysis of the results, a quantitative method was used, structural model equations, through the partial least squares regression method (PLS). The results found were satisfactory, demonstrating that investments in human capital must be the object of public policies, as their influence overlaps the influence of the personal values of each entrepreneur for the expression of quality conventions. The assumptions about the effect of mediation of values in the relationship between human capital and quality worlds are positive and significant, demonstrating that the values had a complementary partial mediation effect between human capital and quality, but with less importance than the direct impact of human capital in quality. It was possible to verify the importance of personal experience, combined with constant training for the development of human capital in the company. In small companies, as is the case with the production of artisanal Brazilian cheeses, in which production and handling are under the control of the family, the contribution of human capital to quality is even more evident. At the same time, personal values have a strong influence on small companies, where the characteristics, behavior, attitudes and beliefs of the entrepreneur are decisive for the results of the enterprise.